2019
DOI: 10.1101/571638
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nicotinamide Deficiency in Primary Open-Angle Glaucoma

Abstract: PURPOSE: To investigate the plasma concentration of nicotinamide in primary openangle glaucoma (POAG).DESIGN: Case-control study METHODS: Plasma of 34 POAG individuals were compared to that of 30 age-and sexmatched controls using a semi-quantitative method based on liquid chromatography coupled to high-resolution mass spectrometry. Subsequently, an independent quantitative method, based on liquid chromatography coupled to mass spectrometry, was used to assess nicotinamide concentration in the plasma from the s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…An additional key difference in metabolic profiles between control and glaucoma retinas was a decrease in retinal nicotinamide (NAM). NAM levels were lower in D2 retinas compared to controls consistent with decreased retinal NAD levels in this model (10) and decreased serum NAM levels in primary open angle glaucoma patients (18). We have previously demonstrated that NAM confers a robust neuroprotection against damaging IOP insults.…”
supporting
confidence: 73%
“…An additional key difference in metabolic profiles between control and glaucoma retinas was a decrease in retinal nicotinamide (NAM). NAM levels were lower in D2 retinas compared to controls consistent with decreased retinal NAD levels in this model (10) and decreased serum NAM levels in primary open angle glaucoma patients (18). We have previously demonstrated that NAM confers a robust neuroprotection against damaging IOP insults.…”
supporting
confidence: 73%
“…In glaucoma models, diets supplemented with niacin have been demonstrated to protect RGCs from degeneration by supporting mitochondrial health and metabolism (14)(15)(16). In this respect, vitamin B3 has been included in the panel of neuroprotective strategies in glaucoma patients in which low vitamin B3 levels have been demonstrated (17). Accordingly, vitamin B3 supplementation appears to counteract RGC dysfunction.…”
Section: Introductionmentioning
confidence: 99%